Wettability and morphology of the leaf surface in cashew tree from the Amazon, Northern Brazil - Glenda Quaresma Ramos; Marta Duarte da Fonseca de Albuquerque; José Luiz Pinto Ferreira; Eduardo Adriano Cotta; Henrique Duarte da Fonseca Filho (Acta Scientiarum: Biological Sciences, 2016)
Leaves surfaces, which represent an interface with plants and the environment, have several structures with specific functions. Some foliar properties, including wettability and mechanical containment, are inferred in terms of cellular adaptation and the presence or absence of cuticular wax. Various morphological parameters, ranging from macro- to nano scales, are analyzed and contribute to the study of taxonomy, pharmacognosy, and ecology of plants. The aim of this paper was to analyze the effect and influence of epicuticular wax granules on the hydrophobicity of Anacardium occidentale L. leaf surfaces. Leaf specimens were directly examined with an environmental scanning electron microscope without metal coating. Images revealed epidermis ornament, stomata type, was, and trichomes. Static contact angle between water and the surface was also measured on both sides. On the adaxial side, an angle of 104.09° ± 0.95° was found, suggesting that adaxial surface is hydrophobic. On the abaxial side, the angle was 62.20° ± 1.60°, which indicates a hydrophilic nature, probably because of the greater amount of epicuticular wax on the adaxial leaf surface. The present investigation provided an important contribution to morphological and ultrastructural characterization of leaves of cashew tree, which is a plant of great medicinal and economic importance.